Державна фінансова інклюзія як драйвер модернізації пенсійної системи України - Трусова, Наталя Вікторівна; Trusova, Nataliia (Запоріжжя : 2023, 2023)
UA: В статті розглянуто державна фінансова інклюзія як драйверу модернізації пенсійної системи України. Сформовано системний підхід до регламентації державної фінансової інклюзії, що забезпечує оптимальну модель фінансування пенсійних виплат та соціальних потреб населення непрацездатного віку, враховуючи модернізовану ієрархію структури пенсійної системи та ефективність її дії при розподілі бюджетних ресурсів. Обґрунтовано, що фінансова інклюзія в системному аналізі державної пенсійної системи є платформою загальної теорії систем, включає в себе низку взаємопов’язаних складових відкритої фінансової система з позиції розподілу бюджетних ресурсів на соціальні потреби населення. Доведено, що системний підходів до використання методологічної парадигми фінансової інклюзії в пенсійній системі акцентує увагу на різних аспектах процесу бюджетного фінансування та відображає концептуальну платформу розвитку пенсійного забезпечення. Представлено моделі пенсійних систем та методика Світового банку за рівнями пенсійного забезпечення. Наведено напрями фінансової інклюзії в пенсійній системі держави в контексті «держава – бізнес – суспільство» та схема оптимізації державне фінансування соціальних програм пенсійної системи. EN: The article considers the policy of state financial inclusion as a driver of modernization of the pension system of Ukraine. A systematic approach to the regulation of state financial inclusion policy and its indicators has been developed, which provides the optimal model for financing pension benefits and social needs of the working age population, taking into account the modernized hierarchy of the pension system and its efficiency in allocating budget resources. It is substantiated that financial inclusion in the system analysis of the state pension system is a platform of the general theory of systems, includes a number of interconnected components of the open financial system from the standpoint of allocation of budgetary resources to social needs. It is proved that the systemic approaches to the use of the methodological paradigm of financial inclusion in the pension system focuses on various aspects of the budget financing process and reflects the conceptual platform for the development of pensions. Models of pension systems and methods of the World Bank according to the levels of pension provision are presented. The directions of financial inclusion in the state pension system in the context of “state – business – society” and the scheme of optimization of state financing of social programs of the pension system are given. The size of pensioners by types and size of pensions in the regions of Ukraine, the coefficient of replacement of lost income in Europe is analyzed. The ratio of the own revenues of the Pension Fund of Ukraine is determined, taking into account the part of the paid single contribution to the obligatory state social insurance, divided into the obligatory state pension insurance to GDP. The total current pension expenditures from GDP in European countries are estimated. The scheme of actuarial calculations of pension provision in the state financial inclusion of the pension system for short-, medium- and long-term periods is proposed.
State financial inclusion as a driver of modernization of the pension system of Ukraine
Keywords: державна фінансова інклюзія; пенсійна система; пенсійне забезпечення; пенсійні виплати; соціальні потреби населення; фінансові ресурси; state financial inclusion; pension system; pension provision; pension payments; social needs of the population; financial resources